The restricted adhesion of bone marrow mesenchymal stem cells by stepped structures on surfaces of hydroxyapatite. Issue 19 (20th April 2022) - Chen, Jin; Huang, Zhuo; Wang, Fang; Gong, Min; Zhang, Xueli; Wang, Yajing; Hu, Zuquan; Zeng, Zhu; Wang, Yun
Abstract : Stepped structures largely exposed on surfaces of HA significantly restrict the adhesion of bone marrow mesenchymal stem cells. Abstract : Currently, many researches have developed several strategies to design the surface structures of hydroxyapatite (HA), and have proved that the surface structures are pivotal in guiding the adhesion of bone marrow mesenchymal stem cells (BMSCs) as well as subsequent cellular behaviours. Most of these strategies, such as altering roughness and constructing surface patterning of HA, involve the construction of geometric topographies at the micro/nanoscale. However, besides geometric topographies, crystal defects are also important characteristics of surface structures and would alter many local physicochemical properties, which is critical for contact between cells and bioceramic surfaces. For the practical applications of crystal defects, a major hindrance is that crystal defects are usually unstable and easily eliminated during crystallization, which limits the large-scale fabrication of materials with crystal defects. In this work, given that stepped structures contain massive stable crystal defects on their step edges and kinks, we proposed a feasible and efficient method to fabricate HA dishes with stepped structures on their surfaces. First, plate-like HA mesocrystals were prepared from CaHPO4 via topotactic transformation, and were shaped into HA dishes by vacuum-filtration. Then, a sintering process was applied to facilitate the formation of stepped structures on the surfaces. We demonstrated that the generation of stepped structures could restrict the adhesion of BMSCs and showed the restriction effect is highly correlated with the density of exposed stepped structures. This phenomenon is interesting and the construction of a cell adhesion model is robust and easy, the underlying mechanisms of which deserve further exploration. Furthermore, constructing stepped structures on surfaces may be a new useful strategy to regulate cell adhesion and could also cooperate with other methods that do not need change in the surface crystal structure.